Magnetotransport properties of Fe0.8Ga0.2 films with stripe domains - Granada, Mara (2016)
Magnetotransport properties of Fe0.8Ga0.2 films with stripe domains are studied. The anisotropic magnetoresistance dominates the low field behavior, which is extremely dependent on the magnetic domains configuration. The magnetoresistance measured at different temperatures displays qualitatively different behaviors depending on the measurement configuration. When the stripes are oriented along the electric current, the low-field magnetoresistance changes sign with temperature, while when the stripes are perpendicular to the electric current the magnetoresistance curves are nearly temperature independent. A simple model considering parallel (series) conduction along (across) the stripes, plus the temperature dependence of anisotropic magnetoresistance and domains configuration, accounts for these experimental results.